The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1016/j.bbabio.2008.05.007
|View full text |Cite
|
Sign up to set email alerts
|

A novel potassium channel in skeletal muscle mitochondria

Abstract: In this work we provide evidence for the potential presence of a potassium channel in skeletal muscle mitochondria. In isolated rat skeletal muscle mitochondria, Ca(2+) was able to depolarize the mitochondrial inner membrane and stimulate respiration in a strictly potassium-dependent manner. These potassium-specific effects of Ca(2+) were completely abolished by 200 nM charybdotoxin or 50 nM iberiotoxin, which are well-known inhibitors of large conductance, calcium-activated potassium channels (BK(Ca) channel)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
48
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 51 publications
2
48
0
Order By: Relevance
“…The electrophysiological properties of this channel were studied in the inner mitochondrial membrane of the human endothelial cell line EA.hy926 using the patch-clamp technique in the mitoplast-attached mode. Large conductance (270 Ϯ 10 pS), voltage dependence, a higher open-state probability at positive potentials, sensitivity to Ca 2ϩ , and NS1619 (a BK Ca channel opener) and paxilline and iberiotoxin (BK Ca channel inhibitors) indicate the similarity of this channel to the mammalian mitoBK Ca channels previously reported in glioma (31), skeletal muscle (33), brain (14,33), and cardiac (40) cells. Interestingly, a mitoBK Ca channel with similar electrophysiological properties (although with a much higher conductance of 502-605 pS) has been recently described in nonmammalian mitochondria (potato tuber) mitochondria (22).…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…The electrophysiological properties of this channel were studied in the inner mitochondrial membrane of the human endothelial cell line EA.hy926 using the patch-clamp technique in the mitoplast-attached mode. Large conductance (270 Ϯ 10 pS), voltage dependence, a higher open-state probability at positive potentials, sensitivity to Ca 2ϩ , and NS1619 (a BK Ca channel opener) and paxilline and iberiotoxin (BK Ca channel inhibitors) indicate the similarity of this channel to the mammalian mitoBK Ca channels previously reported in glioma (31), skeletal muscle (33), brain (14,33), and cardiac (40) cells. Interestingly, a mitoBK Ca channel with similar electrophysiological properties (although with a much higher conductance of 502-605 pS) has been recently described in nonmammalian mitochondria (potato tuber) mitochondria (22).…”
Section: Discussionmentioning
confidence: 53%
“…These studies provide concrete morphological evidence for the existence mitoBK Ca channels (␣-subunit) in the inner mitochondrial membrane of rat brain cells. Moreover, rat skeletal muscle and brain mitochondria show immunoreactivity against antibodies targeting the BK Ca ␤ 4 -subunit (27,32,33). These findings indicate a close molecular similarity between the mitoBK Ca channel and the plasma membrane BK Ca channel, suggesting that both channels are splice variants of the same gene product.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…MitoBK Ca was also found in skeletal muscle (Skalska et al, 2008) and brain (Skalska et al, 2009;Douglas et al, 2006;Fahanik-Babaei et al, 2011a,b). A BK Ca channel is composed of four similar α-subunits that co-assemble around a central axis to form a single K + -selective conduction pore, plus β auxiliary subunits that co-associated with each α-subunits in a 1:1 ratio To date, four β subunits (β1-4) have been described with β1 being the principal form found in vascular smooth muscle cells, while β2 (chromaffin cells, brain, lung), β3 (testis, pancreas, spleen) and β4 (neuronal, lung) are thought to be restricted to other tissues (Orio et al, 2002;Salkoff et al, 2006;Wang et al, 2006).…”
mentioning
confidence: 90%
“…MitoBK Ca (KCa1.1) (reviews [136-138, 181, 200]), displaying a conductance of 100-300 pS, has been observed by direct patch clamping of mitoplasts of mammalian cells [170,196] as well as in planar lipid bilayer experiments [173]. The channel has been identified Fig.…”
Section: Calcium-dependent Potassium Channelsmentioning
confidence: 99%